Analisis kesulitan dalam memahami teks fiksi bahasa indonesia kelas iii di sekolah dasar - Nur Ika Sari; Rukayah Rukayah; Siti Kamsiyati (Didaktika Dwija Indria, 2022)
The purpose of this research is to identify difficulties in understanding fictional texts and the factors causing difficulties in understanding Indonesian fictional texts in grade 3 of SD N Girimargo 1. The method used in this research is descriptive qualitative with a case study approach. Sources of data in this research are the teacher of grade 3 and the students of grade 3 amounting to 6 students. The data collection technique was done by interviews, tests, and documents. The results of this research indicate that difficulties in understanding fictional texts are that students have difficulty in determining the theme of the story, interpreting the vocabulary of the story, analyzing the moral of the story, concluding the story and retelling the story that has been read. Factor that causesing is the learning of Indonesian fictional texts which includes the methods and media used by the teacher, and also caused by psychological factors and fatigue factor felt by students when learning Indonesian fictional texts. The results of this research are intended to develop students' reading comprehension skills so that the difficulties experienced by students can be resolved and can be used as a basis for more relevant research.